2017
DOI: 10.1002/ijc.31132
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids promote a glioma stem cell‐like phenotype and resistance to chemotherapy in human glioblastoma primary cells: Biological and prognostic significance

Abstract: Glioma stem cells (GSCs) are glioblastoma (GBM) cells that are resistant to therapy and can give rise to recurrent tumors. The identification of patient-related factors that support GSCs is thus necessary to design effective therapies for GBM patients. Glucocorticoids (GCs) are used to treat GBM-associated edema. However, glucocorticoids participate in the physiological response to psychosocial stress, which has been linked to poor cancer prognosis. This raises concern that glucocorticoids affect the tumor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
(75 reference statements)
1
20
2
Order By: Relevance
“…We did find an association between medication of corticosteroids and impaired executive functioning. This effect may be interpreted as a result of aggressive tumor growth requiring steroid use, rather than the steroid treatment per se, but direct disease-driving effects of corticosteroids have also been discussed [26].…”
Section: Discussionmentioning
confidence: 99%
“…We did find an association between medication of corticosteroids and impaired executive functioning. This effect may be interpreted as a result of aggressive tumor growth requiring steroid use, rather than the steroid treatment per se, but direct disease-driving effects of corticosteroids have also been discussed [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies found that glucocorticoids could suppress cancer proliferation through activating glucocorticoid receptor [50,51]. For example, Yao and coworkers recently demonstrated that dexamethasone inhibits pancreatic tumor growth in preclinical models.…”
Section: Glucocorticoids and Treatment Of Solid Tumorsmentioning
confidence: 99%
“…In primary GBM cell lines treated with TMZ, the addition of DEX counteracted TMZ-induced apoptosis and caused resistance to nutrient deprivation. 40–42 Furthermore, in vitro DEX administration reduced the bystander effect of the thymidine kinase/ganciclovir system in suicide-gene therapy and reduced the antitumor effect of interleukin-4. 43,44 The alkylating impact of TMZ targets the O 6 -alkylguanin in the carcinogenic lesion, which is reversed by the O 6 -methylguanine-DNA-methyltransferase (MGMT) repair enzyme.…”
Section: Effects Of Dexamethasone In Preclinical Studiesmentioning
confidence: 99%